Profil self-efficacy peserta didik dan implikasinya dalam pelayanan bimbingan dan konseling di sekolah - Joni Abdul Azis; Anna Rufaidah; Nina Mardiana (Orien: Cakrawala Ilmiah Mahasiswa, 2022)
the purpose of this research is to see the level of self-efficacy of students. The research was conducted by survey method. The population in this study was class VIII students of SMP Negeri 2 Cisarua in Bogor Regency with a sample size of 40 students. The sampling technique used is purposive sampling. The research instrument used is the self-efficacy questionnaire, which has been validated and has a reliability of 0.91. Data analysis in this study was carried out using the ordinal or level categorization method based on the normal distribution. The results of the study concluded that Class VIII students at SMP Negeri 2 Cisarua had a level of self-efficacy in the medium category. The results of this study are expected to be useful as a reference for guidance counseling teachers in helping students to be able to improve self-efficacy.